LP44 (4-[2-(methylthio)phenyl]-N-(1,2,3,4-tetrahydronaphthalen-1-yl)-1-piperazinehexanamide) exerts anti-ulcer effects via 5-hydroxytryptamine receptor 7 activation on indomethacin-induced gastric ulcers in rats - Calik, Ilknur; Yayla, Muhammed; Cinar, Irfan; Cadirci, Elif; Albayrak, Abdulmecit; Sirin, Busra; Halici, Zekai (Springer Basel Ag, 2020)
Aim This study aimed to demonstrate the role of serotonin 7 receptor (5-HT7) and the effects of 5-HT7 agonists and antagonists in an indomethacin-induced gastric ulcer. Material and method Male albino Wistar rats (n = 60) were used in the experiments. LP44 (5-HT7 agonist) and SB269970 (5-HT7 antagonist) were administered at 10 mg/kg as a pre-treatment. One hour after the drug treatments, 25 mg/kg of indomethacin (INDO) was administered to all groups except the healthy control group. Six hours after indomethacin administration, all the rats were euthanized. Results We analyzed the iNOS, eNOS, and 5-HT7 receptor mRNA levels in the stomach tissue of rats by real-time PCR. 5-HT7 mRNA expression was increased in the INDO group compared to the healthy group. LP44 administration exerted a significant upregulatory effect on eNOS mRNA expression and downregulatory effects on iNOS and 5-HT7 mRNA expression compared to the INDO group. However, antagonist (SB269970) administration did not result in such difference in gene expression, but even partially decreased the agonist's effect in combination. Famotidine and agonist exerted similar effects. Histopathological findings supported the beneficial effects of 5-HT7 agonist on gastric tissue. Conclusion The study suggested that activation of 5-HT7 receptor showed a significant anti-ulcerogenic effect in the indomethacin-induced gastric ulcer model.
Keywords: 5-HT7; Rat; Ulcer; eNOS; iNOS